Acral fibromyxoma: a rare plantar nodule. Issue 6 (24th June 2022) - Sivasaththivel, Malini; Howard, Matthew David; Yazdabadi, Anousha
Abstract : Acral fibromyxomas are benign tumours ranging in size between 0.6 and 5 cm, commonly found around the nailbed. The often asymptomatic presentation of acral fibromyxomas means that there is often a delay in their diagnosis and subsequent treatment. The objective of this paper is to present the unique case of a fibromyxoma present in the acral region, as well as a review of the literature.